Biblical Deborah and Mary Mitchell Slessor â€“ A Comparison in Time and Space - Eyo, Ubong E. (PINISI Discretion Review, 2020)
This paper investigates â€œBiblical Deborah and Mary Mitchell Slessor â€“ A Comparison in Time and Space and Lessons for Contemporary Africa.â€ Worthy of note is the fact that, for some of the religions of the world women are a problem; from time immemorial they have been subordinate to men, second-class in the family, politics and business, with limited rights and even limited participation in worship. This was not different from the epochs of both biblical Deborah (Judges 4-5) and Mary Mitchell Slessor, the White Queen of Okoyong. In the time where patriarchy was the rule of the day, there arose two women at different places, times yet with similar circumstances to salvage the people and bring about Godâ€™s mission to the human race. Though both operated within the context of the mission of the church, theirs was missio dei not missio ecclesia, because in their age, missio ecclesia used more of patriarchal instruments while mission dei was/is involve in using human and the entire inhabited world (oikoumenÄ“). The peculiar things about the epochs of both Deborah and Mary Slessor are best described in the text, "...in the days of Jael, the roads were abandoned; travelers took to winding paths. Village life in Israel ceased, ceased until I, Deborah, arose, arose a mother in Israelâ€ (Judges 5:6-7). Both characters are worth studying in close comparison with each other, and this is one of the reasons for this paper. Drawing insights from both characters using historical methodology in the study of religion and the Feminist Biblical Hermeneutics of the Reconstruction of Biblical History among other feminist theories as approaches in evaluating Judges 4 & 5 and content analysis research methodology in respect of the life of Biblical Deborah and the life of Mary Mitchell Slessor, the work concludes that in the missio dei, Godâ€™s whose plan is for an egalitarian society uses all genders equally to bring to pass Godâ€™s mission. The significant of this work lies not only in it providing a tool for further academic research but in the lessons to be drawn for the present political and religious dispensation in Africa in particular and the world in general.